Combating hunger and achieving food security - Swaminathan, M. S. (Monkombu Sambasivan) (Cambridge : Cambridge University Press, 2015)
The issues that need to be addressed in combating hunger and achieving food security are highlighted in this book by a great Indian geneticist. It also discusses the major causes of chronic and hidden hunger and emphasises the need to redesign the farming system based on nutritional considerations. The role of an effective monsoon management programme to maximise its benefits is examined. There are chapters that analyse the importance of biodiversity conservation and enhancement and farmer skill development. Important issues to increase agricultural production including investment by financial institutions in agriculture and rural development, women's role in agriculture and youth employment in rural livelihoods are discussed in great detail in the text. The book concludes that there must be synergy between scientific knowledge, political will and farmers' active participation to achieve the goal of overcoming chronic and hidden hunger in the populations of developing countries.
Title from publisher's bibliographic system (viewed on 01 Jan 2016).
Keywords: Agriculture -- Economic aspects -- India; Agriculture -- India; Food supply -- India; Food security -- India; Farm management -- India